Manifestation Of Nihilism As A Destructive Social Phenomenon Of Society - Safarova Markhabo Khalimovna (Peerian Journals Publishing, 2024)
This article explores that nihilism emerged as a continuous social phenomenon in society in the history of human development, and often its interpretations are close to the fanatical spirit. Also, the author categorised the views of scholars who studied these processes
Keywords: nihilism; social instability; approaches; dogmas